PSYCHIATRIC CO-MORBIDITY IN CHRONIC PAIN DISORDER: Psychiatric Co-Morbidity - ., Lt Col Ahmed Shoaib; ., Naila Yaqoob; ., Asjad Sharif (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the psychiatric co-morbidity in patients with chronic pain disorder in hospital setting. Design: Cross sectional descriptive study. Place and duration of study: This study was conducted at Combined Military Hospital (CMH) Okara from June 2011 to May 2012. Patients and Methods: A purposive sample of 400 patients (males=117; females=283) gathered from pain clinic and other outpatient departments of the hospital and were interviewed in detail and Present State Examination was carried out. Demographic variables were scored using descriptive statistics and results were analyzed using correlation methods. Results: It was revealed that psychiatric illness in overall sample prevailed among 266 participants (67%). Among which 164 participants (62%) were diagnosed with depression, 67 patients (25.2%) of chronic pain were diagnosed with anxiety disorders, 28 patients (11%) with adjustment disorder and 1.5% and 1.1% diagnosed with drug dependence and somatization disorder, respectively. Conclusion: Psychiatric co-morbidity especially the incidence of depression, anxiety and adjustment disorders were high amongst patients suffering from chronic pain disorder.